TELAAH PENDAPAT IBN QAYYIM AL-ZAWJIYAH TENTANG HUKUM TAWAF BAGI WANITA HAID - Yunarti, Sri; Dedi, Syarial (AL-ISTINBATH : Jurnal Hukum Islam, 2026)
The aims in this study is to construct women's jurisprudence by examining Ibn Qayyim's ijtihad regarding the permissibility of menstruating women performing tawaf. This is very interesting because there are clear provisions in the texts (the Qur'an and hadith) that prohibit such practice. Tawaf must be performed in a state of purity, considering that the ritual is performed inside the mosque, while there is a prohibition on entering the mosque in conditions of major impurity. This clearly shows the conflict between the texts and the product of ijtihad. This paper is a normative research in the form of a study of figures and is classified as literature research, commonly called qualitative research, and is supported by the approaches of fiqh and ushul al-fiqh. The data used is secondary data. Data collection was carried out by reading books by the figures discussed, namely: A’lam al-Muwaqiin an rab al-‘Alamin, by including literature related to this issue. The data analysis is inductive, consisting of content analysis through data reduction, data display, and a conclusion. This study concludes that Ibn Qayyim's opinion, which permits women to perform tawaf during menstruation, does not negate sacred law or ignore the provisions of the texts and the opinions of scholars, but rather links the provisions of the texts with sharia principles. This line of thinking pays close attention to the social conditions of society. This legal fatwa is still relevant to practice and can save women from the risks of consuming period-delaying pills.